2000
DOI: 10.2514/2.4667
|View full text |Cite
|
Sign up to set email alerts
|

Gain-Scheduled Control: Relaxing Slow Variation Requirements by Velocity-Based Design

Abstract: This paper investigates the application of the gain-scheduling approach to flight control tasks where the conditions required by conventional techniques need not be satisfied. The conditions required by conventional techniques are progressively relaxed and the design of gain-scheduled controllers under a range of conditions is addressed. In particular, the paper considers gain-scheduled control design in situations where the vehicle is manoeuvring aggressively far from equilibrium, the airspeed need not be slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 15 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…These traditional gain-scheduling conditions are, however, conservative in nature. By nonlinear analysis of the resulting closed-loop system, the classical gain-scheduling approach (including the foregoing, on the face of it rather ad hoc, implementation technique) may lead to a soundly based controller design which is globally valid (not restricted to near equilibrium operation) provided that appropriate conditions are satisfied (Leith & Leithead, 2000b). Namely, it is required that the aerodynamic moment and force are linear with respect to lateral velocity and fin angle and that qN=qv; qN=qr; qN=qd; qY=qv and qY=qd do not depend on the lateral velocity, v; or the fin angle, d; that is,…”
Section: Control Design Taskmentioning
confidence: 99%
See 2 more Smart Citations
“…These traditional gain-scheduling conditions are, however, conservative in nature. By nonlinear analysis of the resulting closed-loop system, the classical gain-scheduling approach (including the foregoing, on the face of it rather ad hoc, implementation technique) may lead to a soundly based controller design which is globally valid (not restricted to near equilibrium operation) provided that appropriate conditions are satisfied (Leith & Leithead, 2000b). Namely, it is required that the aerodynamic moment and force are linear with respect to lateral velocity and fin angle and that qN=qv; qN=qr; qN=qd; qY=qv and qY=qd do not depend on the lateral velocity, v; or the fin angle, d; that is,…”
Section: Control Design Taskmentioning
confidence: 99%
“…It is, therefore, also necessary to ensure that the state-space realisations of the members of the controller linearisation family are suitably compatible with one another. When the rate of variation of a nonlinear system is sufficiently slow, it can be shown that the controller becomes insensitive to the choice of realisation (Leith & Leithead, 2000b). However, in general, it is straightforward to confirm the closed-loop dynamics may be extremely sensitive to the choice of realisation.…”
Section: Velocity-based Gain-scheduling Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…In this approach, the system is linearized at multiple trimmed flight conditions throughout the flight envelope and a corresponding set of linear controllers are defined. Then overall attitude control system is realized with scheduled gains defined by interpolation online with respect to some meaningful flight conditions such as dynamic pressure, Mach number, etc [5,6]. However, the design of gain scheduling controller is time-consuming and relies extensively on experience of control designers.…”
Section: Introductionmentioning
confidence: 99%
“…Since the flight dynamics have nonlinear nature, the linear approximation of the system leads to controllers with stability and performance limitations. To overcome such limitations there exist in the literature a variety of control methodologies which provide important advances in GSC and hybrid and nonlinear approaches [5][6][7][8]; see also GSC surveys [1,[9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%